Internet Advertising and the Generalized Second-Price Auction: Selling Billions of Dollars Worth of Keywords - Edelman, Benjamin; Ostrovsky, Michael; Schwarz, Michael (American Economic Review, 2007)
We investigate the "generalized second price" auction (GSP), a new mechanism which is used by search engines to sell online advertising that most Internet users encounter daily.GSP is tailored to its unique environment, and neither the mechanism nor the environment have previously been studied in the mechanism design literature.Although GSP looks similar to the Vickrey-Clarke-Groves (VCG) mechanism, its properties are very different.In particular, unlike the VCG mechanism, GSP generally does not have an equilibrium in dominant strategies, and truth-telling is not an equilibrium of GSP.To analyze the properties of GSP in a dynamic environment, we describe the generalized English auction that corresponds to the GSP and show that it has a unique equilibrium.This is an ex post equilibrium that results in the same payoffs to all players as the dominant strategy equilibrium of VCG.